The Emotional Gaze: A Symbol Of My Mother’s Deep Reflections In Term Of Artwork - Abdul Razak, Ruzamira; Abdullah, Ramlan (Idealogy Journal; Vol 4 No 2 (2019): Idealogy Journal (September 2019)DO - 10.24191/idealogy.v4i2.153, 2019)
My mother, Rusimah Ibrahim relates the thoughts of contemporary mother, living in a petty apartment with her out-of-work husband with her three toddlers, who must take care for the foods, schools, pay the bills and every single thing. The pressure of my mother felt for the half of her life is not a barrier to survive. It is because she held on to a principle that she believed would be able to change the behaviour of my father. As an artist, I took this opportunity to study my own lives and record my experience, in this way which the way I love. In the way that gives evidence. This thesis marked my process of collecting her struggles and suffer into a documented narrative based on my own perspectives and interpretations. This thesis work, I transform her facial’s entire identity into something substantial. As I reflected on the impact and meaning of my mother’s life story as a conduit for the art process, I felt extremely fragmented in my own personal reactions and recollections towards her suffer. Therefore, I treat each painting individually as I respond to her experience and memory that I hold. Moreover, each artwork approaches different stage of her experience. As a painter, I choose watercolour medium as my tools to represent the idea. Somehow I felt increasingly cognizant of how my mother and I became closer and my feelings and attitudes changes toward our relationship started to resemble in my artworks. However, my intention would stick in one agenda which to produced artworks and being honest I personally think that the findings are enticing, nevertheless. Keywords: My mother, The Gaze, Emotional, Personal Experience, Deep Reflections.